2021
DOI: 10.1038/s41598-021-98595-4
|View full text |Cite
|
Sign up to set email alerts
|

New early phenotypic markers for cucumber green mottle mosaic virus disease in cucumbers exposed to fluctuating extreme temperatures

Abstract: Studies of early stages of cucumber green mottle mosaic virus (CGMMV) disease have been recently focused on plant molecular responses. However, extreme diurnal environmental temperatures, characteristic of global climate changes, could affect plant susceptibility and disease phenotype progression. Our studies of CGMMV disease progression, under simulated extreme temperature waves, have revealed two new disease initiation phenotypes that developed gradually, preceding severe symptom manifestations of post-recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…Cucumber plants cvs. Romi and Senyal were cultivated, as previously described, and inoculated with CGMMV-Rd purified inoculum [18]. Treated plants were grown in temperature-controlled growth chambers and disease-symptom manifestations were monitored closely.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cucumber plants cvs. Romi and Senyal were cultivated, as previously described, and inoculated with CGMMV-Rd purified inoculum [18]. Treated plants were grown in temperature-controlled growth chambers and disease-symptom manifestations were monitored closely.…”
Section: Methodsmentioning
confidence: 99%
“…Serological analyses were performed, as previously described, using ELISA tests for systemically infected plants and Western blots for dissected equal sizes of EBYIs and the corresponding DGS tissues [18]. Meteorological data was extracted from records on the Israeli Meteorology Services (IMS) website: https://ims.gov.il/he/ObservationDataAPI (accessed on 10 November 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that the seasonal disease in tomatoes, which were observed primarily during the hot summer weather, has become more severe in the cold weather due to synergism occurring between ToBRFV and a mild potexvirus pepino mosaic virus (PepMV-IL) [19,20]. Regarding CGMMV, we have recently shown a tight correlation between disease manifestations and fluctuating environmental temperatures [21,22].…”
Section: Introductionmentioning
confidence: 99%